The anatomy of marital happiness - Sam Peltzman (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Since 1972, the General Social Survey has periodically asked whether people are happy with Yes, Maybe or No type answers. Here I use a net "happiness" measure, which is percentage Yes less percentage No with Maybe treated as zero. Average happiness is around +20 on this scale for all respondents from 1972 to the last pre-pandemic survey (2018). However, there is a wide gap of around 30 points between married and unmarried respondents. This "marital premium" is this paper's subject. I describe how this premium varies across and within population groups. These include standard socio demographics (age, sex, race education, income) and more. I find little variety and thereby surface a notable regularity in US socio demography: there is a substantial marital premium for every group and sub-group I analyze, and this premium is usually close to the overall 30-point average. This holds not just for standard characteristics but also for those directly related to marriage like children and sex (and sex preference). I also find a "cohabitation premium", but it is much smaller (10 points) than the marital premium. The analysis is mainly visual, and there is inevitably some interesting variety across seventeen figures, such as a 5-point increase in recent years.
Keywords: D10; D60; I31; J10; J12; J18; K360; Z13; 330; happiness; marriage; demographics; family; education; income; sex; sex preference